Controlling texture in processed meat production - MORADIANNEJAD, HESAM (2017)
The present study showed the effects of a number of hydrocolloids in terms of adding them dry, pre-hydrated or solubilised and gelled, using unmodified wheat starch, 3 types of carrageenan (kappa, iota and lambda), locust bean gum (LBG), and finally citrus fibre on meat stability, textural properties, and microstructure. The study further elucidated the role of heat induced gelation in texture formation of processed meat products. The finding of the study revealed that the maximum hardness related to the dry state of all hydrocolloids when added to a product containing 65% meat (i.e. 7.4% unmodified wheat starch, 1% LBG and 3% citrus fibre, except the carrageenan treatment, which is related to 2% gelled kappa carrageenan). Furthermore, the elasticity or rubbery texture of the sausages increased with 3% pre-hydrated wheat starch, 1 % dry LBG and citrus fibre and finally 1% solubilised kappa carrageenan with 65% meat. However, ameliorating elasticity of LBG and citrus fibre, which are 1 and 3%, respectively, took place with the dry state. The Differential Scanning Calorimetry (DSC) results showed that starch and carrageenan showed clear irreversible and reversible transitions, respectively, on the timescale of the experiment in the region of 60˚C, whereas locust bean gum and citrus fibre showed no transitions. No interaction between carbohydrates and proteins was signalled by the transition temperatures of the unaffected transitions and the addition of enthalpies which was linear. The rheology result indicated that storage modulus (G´) was greater than the loss modulus (G˝) during the test (G´> G˝), which implied predominant elastic behaviour of the sample for the whole range of deformation experimented. Finally, confocal scanning laser microscopy (CSLM) demonstrated that the void space is augmented (visa-a-vis the control sample of 65% meat) after adding dry LBG. However, the size of cavity shrank after adding gelled kappa carrageenan, dry citrus fibre, and dry wheat starch. In all treatments, the fat droplet decreased in mean size in the wake of adding hydrocolloids in the systems. Both of these findings indicate that an increase in batter texture upon the addition of hydrocolloids was sufficient to break up air cells and emulsion droplet, and then had enough strength to maintain the smaller cells droplets. The findings of the study in hand, provide a new approach to meat product manufacturing.